Thickness Uniformity Assessment of Epoxy Asphalt Pavement Layer on Steel Bridge Decks Using Three-Dimensional Ground-Penetrating Radar - Lei Huang; Zhijian Jin; Zhian Yao; Bo Chen; Weixiong Li; Xuetang Xiong; Huayang Yu (Buildings)
To address the challenge of assessing the thickness uniformity of epoxy asphalt layers on steel bridge decks, three-dimensional ground-penetrating radar (3D-GPR) was employed for non-destructive, full cross-sectional detection of the pavement layer’s thickness. The antenna array spacing was optimized using the common midpoint (CMP) method, enabling precise measurement of the relative permittivity of epoxy asphalt mixtures. A significant correlation between relative permittivity and the void ratio was established, providing a novel approach to identifying areas prone to coarse segregation and early-stage water damage. Grayscale maps of the thickness distribution enabled precise detection of regions with acceptable, under-thickness and over-thickness values. The uniformity of construction thickness was quantitatively evaluated using standard deviations and coefficients of variation. Results indicated that when the coefficient exceeds 12%, improvements in the pavement construction process are necessary. This research demonstrates the capability of 3D-GPR to effectively detect thickness variations, offering a valuable tool for enhancing pavement paving and compaction practices on steel bridge decks.